TINJAUAN EMPIRIS FENOMENA PROSTITUSI PEKERJA SEKS KOMERSIAL DALAM KAJIAN SOSIOLOGI HUKUM - Oktavia Musu, Citra Trifena; Apriani, Rani (Peneliti.net, 2024)
Prostitution is an act committed by a person or group of people whose purpose is to trade a person or persons for profit. Law Number 1 of 1946 concerning the Criminal Code is the answer to the problem of prostitution that occurs. However, with the rapid development of technology, it is possible for variations of prostitution to be carried out in an easier and easier way, namely through online media. Article 506 of the Criminal Code is to punish those who become pimps/pimps/brokers/service providers, and the position of women commercial sex workers as victims. However, with the development of modern prostitution providing wide access even not only to pimps/pimps/brokers/service providers as perpetrators, female commercial sex workers are also part of the perpetrators if they sell themselves on their own volition and not coercion from others. On this basis, more specific legislation regarding online prostitution was formed. The results of this study are to describe the formulation of articles 296 and 506 of the Criminal Code and associated with the legislation below which is more specific and then describe the obstacles that occur in law enforcement of online prostitution and the efforts made in eradicating the crime of online prostitution.